How well do national and local policies in England relevant to maternal and child health meet the international standard for non-communicable disease prevention? A policy analysis. Issue 11 (12th November 2018) - Penn-Newman, Daniel; Shaw, Sarah; Congalton, Donna; Strommer, Sofia; Morris, Taylor; Lawrence, Wendy; Chase, Debbie; Cooper, Cyrus; Barker, Mary; Baird, Janis; Inskip, Hazel; Vogel, Christina
Abstract : Objectives: (1) To identify national policies for England and local policies for Southampton City that are relevant to maternal and child health. (2) To quantify the extent to which these policies meet the international standards for nutrition and physical activity initiatives set out in the WHO Global Action Plan for the Prevention and Control of Non-Communicable Diseases (WHO Action Plan). Design: The policy appraisal process involved three steps: (1) identifying policy documents relevant to maternal and infant health, (2) developing a policy appraisal framework from the WHO Action Plan, and (3) analysing the policies using the framework. Setting: England and Southampton City. Participants: 57 national and 10 local policies. Results: Across both national and local policies, priority areas supporting public health processes, such as evidence-based practice, were adopted more frequently than the action-oriented areas targeting maternal and child dietary and physical activity behaviours. However, the policy option managing conflicts of interest was rarely considered in the national policies (12%), particularly in white papers or evidence-based guidelines. For the action-oriented priority areas, maternal health policy options were more frequently considered than those related to child health or strengthening health systems. Complementary feeding guidance (9%) and workforce training in empowerment skills (14%) were the least frequent action-oriented policy options adopted among the national policies. The maternal nutrition-focused and workforce development policy options were least frequent among local policies adopted in 10% or fewer. Macroenvironmental policy options tended to have a lower priority than organisational or individual options among national policies (p=0.1) but had higher priority among local policies (p=0.02). Conclusions: Further action is needed to manage conflicts of interest and adopt policy options that promote a system-wide approach to address non-communicable diseases caused by poor diet and physical inactivity.